2022
DOI: 10.1097/sle.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Use of Critical View of Safety and Proctored Preceptorship in Preventing Bile Duct Injury During Laparoscopic Cholecystectomy—Experience of 3726 Cases From a Tertiary Care Teaching Institute

Abstract: Introduction: Bile duct injury (BDI) continues to occur despite technological advances and improvements in surgical training over the past 2 decades. This study was conducted to audit our data on laparoscopic cholecystectomies performed over the past 2 decades to determine the role of Critical View of Safety (CVS) and proctored preceptorship in preventing BDI and postoperative complications. Materials and Methods: All patients undergoing elective laparoscopic cholecystectomy were analyzed retrospectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In a study by Duca et al ( 3 ), GB perforation was 15.9%, while bleeding was 2.3%. In another study, the bleeding was 5.1% and they used drain in 26.5% of the cases ( 17 ), and others reported GB perforation in 4.9% of cases, bleeding in 0.4% and stone spillage in 2.5% ( 19 ). In a comprehensive study conducted by Nassar et al ( 27 ), the CR was reported at 0.49%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study by Duca et al ( 3 ), GB perforation was 15.9%, while bleeding was 2.3%. In another study, the bleeding was 5.1% and they used drain in 26.5% of the cases ( 17 ), and others reported GB perforation in 4.9% of cases, bleeding in 0.4% and stone spillage in 2.5% ( 19 ). In a comprehensive study conducted by Nassar et al ( 27 ), the CR was reported at 0.49%.…”
Section: Discussionmentioning
confidence: 96%
“…According to a systematic review and meta-analysis in China, the incidence rate of BDI was 1.12% (16). In a large study in India (17), it was 0.05%, and in a local study (Sulaimani, Kurdistan region, Iraq) (18), it was 0.4%. However, a study by Buddingh et al (4) from the Netherlands showed a significantly lower rate of major BDI after the implementation of routine IOC (1.9 vs. 0%).…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 ] In the early years of its use, there was an unacceptable high incidence of bile duct injury which reduced with growing experience all over the world. [ 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%